Was treibt staatliche Umverteilung? - Norbert Berthold; Klaus Gründler; Sebastian Köllner (Wirtschaftsdienst, 2016)
– This paper investigates the major drivers of governmental redistribution. Extended and harmonised data on effective redistribution recently provided by the newest version of the Standardized World Income Inequality Database allows for the assessment of the origins of governmental redistribution for a broad sample of countries. Our findings confirm the Meltzer-Richard hypothesis, pointing to a robust positive relationship between market inequality and redistribution. We show that perceptions of inequality are often biased and that the redistribution-enhancing effect of gross inequality is even stronger when individuals are aware of national income disparities. The results also suggest that top income shares tend to impede redistributive policies.
Keywords: D31; D72; H11; 330; Verteilungspolitik; Umverteilung; Verteilungswirkung; OECD-Staaten